2008
DOI: 10.1002/jmv.21272
|View full text |Cite
|
Sign up to set email alerts
|

Absence of transmission of potentially xenotic viruses in a prospective pig to primate islet xenotransplantation study

Abstract: Shortage of human donor organs for transplantation has prompted usage of animals as an alternative donor source. Pigs are the most acceptable candidate animals but issues of xenozoonoses remain. Despite careful monitoring of designated pathogen free pigs there is still a risk that their tissues may carry infectious agents. Thus xenotransplantation requires extensive pre-clinical study on safety of the graft especially for those viruses that are either potentially oncogenic and/or immunosuppressive, or can esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 52 publications
1
60
0
Order By: Relevance
“…There was no evidence for transmission of any of these pig viruses into the primate recipients (116).…”
Section: Pervsmentioning
confidence: 92%
“…There was no evidence for transmission of any of these pig viruses into the primate recipients (116).…”
Section: Pervsmentioning
confidence: 92%
“…In terms of overall success, despite several studies demonstrating the transmission of PERV in vivo (Argaw, ColonMoran & Wilson, 2004;Martina, Marcucci, Cherqui, Szabo, Drysdale et al, 2006;Popp, Mann, Milburn, Gibbs, McCullagh et al, 2007), no report has conclusively demonstrated productive infection (Denner, Specke, Karlas, Chodnevskaja, Meyer et al, 2008;HermidaPrieto, Domenech, Moscoso, Diaz, Ishii et al, 2007;Levy, Argaw, Wilson, Brooks, Sandstrom et al, 2007;Moscoso, Hermida-Prieto, Manez, Lopez-Pelaez, Centeno et al, 2005;Paradis, Langford, Long, Heneine, Sandstrom et al, 1999;Specke, Schuurman, Plesker, Coulibaly, Ozel et al, 2002). In terms of in vivo transmission from the AI pig herd no evidence of PERV infection was found in non-human primates following transplantation of islet cells (Garkavenko, Dieckhoff, Wynyard, Denner, Elliott et al, 2008) or in twelve human patients sampled from the New Zealand clinical trial (Wynyard, 2011).…”
Section: Perv Infectivity In Vivomentioning
confidence: 97%
“…Breeding the animals under designated pathogen free (dpf) conditions will prevent at least the transmission of known zoonotic microorganisms such as circoviruses, herpesviruses and others [79]. Porcine cytomegalovirus (PCMV), porcine lymphotropic herpesvirus (PLHV), and porcine circovirus (PCV) are the main viruses screened for in the ongoing New Zealand clinical trial [80,81]. In contrast to these microorganisms transmission of porcine endogenous retroviruses (PERVs) cannot be prevented by dpf breeding since they are integrated as DNA copy in the genome of all pigs [101].…”
Section: Microbiological Safetymentioning
confidence: 99%